Mechanism of High Photosynthetic Capacity in BC2F4 LinesDerived from a Cross between Oryza sativa and Wild Relatives O. rufipogon - Chisato Masumoto; Takashige Ishii; Tomoko Hatanaka; Naotsugu Uchida (Plant Production Science, 2005)
We found that several BC2F4 lines had high leaf photosynthetic rates under light-saturated and ambient CO2 conditions. These lines are progenies of BC2F1 plants with high photosynthetic capacities which were generated by backcrossing between Oryza rufipogon (W630) and O. sativa cv. Nipponbare, as a recurrent parent. Some photosynthetic characteristics of the BC2F4 lines were investigated to identify the factors increasing photosynthetic rates. Photosynthetic rates of these lines under light-saturated conditions at 50 to 700 ppm CO2 concentrations were higher than those in Nipponbare. The estimated-maximum photosynthetic rates under light-saturated and CO2-saturated conditions in BC2F4 lines were also higher than that in Nipponbare. The photosynthetic rate under light-saturated and ambient CO2 conditions was positively correlated with the carboxylation efficiency as an indicator of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) activity in vivo rather than stomatal conductance. Initial and total Rubisco activities in vitro tended to be higher in the BC2F4 lines than in Nipponbare. The content of active Rubisco calculated from the activation state of Rubisco was also higher in the BC2F4 lines than in Nipponbare. These results suggest that high photosynthetic capacities of BC2F1 plants can be maintained high in their progenies and high photosynthetic rates under light-saturated and ambient CO2 conditions in the BC2F4 lines are achieved mainly by the high activity of Rubisco due to the high active Rubisco content.